Trace Elements and Their Management in Dialysis Patients—Pathophysiology and Clinical Manifestations - Shu Wakino (Kidney and Dialysis, 2023)
Recently, as the number of elderly dialysis patients has been increasing, complications associated with low nutritional status such as infectious disease have had a strong influence on the prognosis of dialysis patients. Nutritional disorders are caused by the inadequate intake of the three major nutrients—proteins, fats, and carbohydrates—as well as vitamin and mineral deficiencies. Minerals are composed of various elements, including small-amount elements and trace elements, which are present in the human body in very small quantities lower than that of iron. In dialysis and predialysis patients, zinc, manganese, and selenium are the three major elements that are significantly depleted as compared to normal subjects; these deficiencies are sometimes symptomatic. Zinc deficiency is manifest as anemia, taste abnormality, and delayed wound healing, while selenium deficiency is associated with impaired cardiac function and immunocompromised condition. Zinc has multiple functions, since various enzymes, including DNA polymerase and RNA polymerase, need zinc as a cofactor, while selenium is a component of selenoproteins, including glutathione peroxidase and thioredoxin reductases, which are major antioxidative stress enzymes. These elements can only be supplemented exogenously and contribute to the sustainable QOL of dialysis patients. On the other hand, as regards other trace elements, including copper, chromium, manganese, lead, arsenic, etc., the association of their deficiency or intoxication with various involvements of dialysis patients were investigated, although all investigations were performed in cross-sectional studies or observational studies. Therefore, the supplementation of these elements is inconclusive, given the scarcity of other intervention studies. More conclusive studies are endorsed for the establishment of proper supplementation strategies.